Taxa mínima de infecção por Ehrlichia minasensis sp. nov. em carrapatos Amblyomma sculptum e Rhipicephalus microplus e avaliação do perfil sorológico e de infecção em bovinos - Carvalho, Izabelle Thayná Soares (2016)
A new specie phylogenetically closet o Ehrlichia canis has been identified infecting cattle and deer in Canada as well as in cattle and Rhipicephalus microplus ticks in Brazil. This specie was recently classified as Ehrlichia minasensis sp. nov. and although it has been detected in R. microplus, little is known about the epidemiology of this infection, especially in tick species. This study evaluated the infection UFMTBV genotype of E. minasensis in populations of Rhipicephalus microplus, Amblyomma sculptum ticks and in places where naturally infected animals have previously been identified and also the dynamics of the infection of this bacterium in dairies cows in late pregnancy third as well as their calves. For natural infection detection in ticks, the samples were subjected to DNA extraction, individually or in pools, and later amplification of a fragment of the genes dsb, 16S rRNA, and TRP36 through Chain Reaction Polymerase (PCR). A total of 45 ticks after changes [43 adults pools (MIR 13.4%) and 2 nymphs pools (MIR 4%)] and 42 engorged female post-oviposition (MIR 30.6%) were positive for Ehrlichia sp. Obtaining a total of 87 R. microplus samples positive for Ehrlichia spp. (MIR of 17.1%, 95% 14.01 20.75%). The generated partial sequences were 99-100% similar to the sequence of the dsb gene of E. minasensis genotypes UFMG-EV and UFMT-BV, respectively, 100% similar to the sequence 16S rRNA for E. minasensis BOV2010 Canada, and 99% similar to the sequence TRP36 UFMT-BV genotype. No tick sample of A. sculptum detected Ehrlichia sp on PCR. Four cows in late pregnancy third had antibody titers, by indirect immunofluorescence assay (IFA), which decreased in the peri-partum period and increased again in the postpartum period, while the calves had floating antibody titers up to about 75 days, when there was an increase. Was observed the occurrence of transestadial transmission of Ehrlichia in R. microplus ticks, and therefore its possible participation in the epidemiology and transmission of ehrlichiosis in cattle. Through the monitoring of dairy cattle by IFA and PCR, it was possible to obtain important information on the dynamics of natural infection with Ehrlichia sp. the animals sampled, which allowed for inferences about the relationship between pathogen, susceptible hosts and potential vectors in conditions of natural infection.